Efforts To Prevent Stunting Through Dental And Oral Health Services For Pregnant Women In The Posyandu Working Area Of Penebel Ii Puskesmas Tabanan District - Kencana, I Gede Surya; Budi Artawa, I Made; Gejir, I Nyoman (Jurnal Pengabmas Masyarakat Sehat, 2025)
Abstract Stunting is a global health problem that impacts children's growth and development. One of the factors that influences stunting is the mother's health during pregnancy, including dental and oral health. Dental health problems in pregnant women can affect nutritional intake and overall health. The aim of this community service program is to increase knowledge and awareness of pregnant women about the importance of dental and oral health and to prevent problems that can affect maternal health and the risk of stunting in babies. Method: Counseling on maintaining oral health and dental hygiene examinations of pregnant women. The results of the level of knowledge of pregnant women regarding dental health maintenance were 3 people (6.1%) with good criteria and 34 people (69.4%) with poor criteria. The average level of knowledge for pregnant women is 58 (less). The level of dental and oral hygiene of pregnant women at the Penebel II Community Health Center was 39 people (79.6%), the level of dental and oral hygiene was moderate and 2 pregnant women (4.1%) had good criteria. After attending counseling and education, pregnant women will have a better understanding of the importance of maintaining healthy teeth and mouth during pregnancy. They understand the relationship between oral health and the risk of stunting in babies born, as well as the importance of proper nutritional intake and reducing the OHI-S index in pregnant women